Endoscopic retrograde cholangio-pancreatograhy and laparoscopic cholecystectomy in single session management of acute biliary pancreatitis - Gaber, Ahmed; Ammar, Mohamed S.; Soltan, Hatem (International Surgery Journal, 2017)
Background: World widely, the annual incidence of acute pancreatitis ranges from 5 to 50 per 100000. The major cause of acute pancreatitis is biliary calculi, which occur in 50-70% of patients. Aim of this study is to evaluate Endoscopic Retrograde Cholangio-Pancreatography (ERCP) and Laparoscopic Cholecystectomy (LC) as a single step management of early acute biliary pancreatitis. Methods: A prospective study included 25 patients complaining of acute biliary pancreatitis. The study was done between December 2012 and February 2016 at Menofia University Hospital. All patients had acute biliary pancreatitis with obstructive jaundice proved by laboratory investigations and imaging. ERCP and LC in the same session were aimed in all patients. Results: Successful same session was done in 24 (96%) cases and 1 (4%) case failed (just had ERCP only). Twenty cases (80%) were females and five cases (20%) were males. By ERCP, multiple small stones were extracted in 15 (60%) cases, biliary mud in 3 (12%) cases, a big stone in 2 (8%) cases and no stones were extracted in 5 (20%) cases. During laparoscopic cholecystectomy, bile stained ascites was present in 15 (60%) cases and absent in 9 (36%) cases. Calcium soap in 7 (28%) cases and absent in 17 (68%) cases. 17 (68%) patients stayed 24 hours in hospital while 6 (24%) patients stayed 48 hours and 2 (8%) cases stayed 72 hours. No mortality was recorded. Conclusions: ERCP and LC as a single step is a good option for management of early acute biliary pancreatitis.